2016
DOI: 10.3390/rs8110904
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Uncertainty Estimation of the Latest Radar and Satellite Snowfall Products Using SNOTEL Measurements over Mountainous Regions in Western United States

Abstract: Snow contributes to regional and global water budgets, and is of critical importance to water resources management and our society. Along with advancement in remote sensing tools and techniques to retrieve snowfall, verification and refinement of these estimates need to be performed using ground-validation datasets. A comprehensive evaluation of the Multi-Radar/Multi-Sensor (MRMS) snowfall products and Integrated Multi-satellitE Retrievals for GPM (Global Precipitation Measurement) (IMERG) precipitation produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…Most of the IMERG assessment studies were conducted in Asia. It should be noted that several other IMERG assessment studies were conducted in Western countries, for example, [17,18], but they did not perform the daily scale assessment and were therefore excluded from this comparison. To date, the IMERG's daily precipitation was found to have a very good correlation with ground-based precipitation in China [16,38,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the IMERG assessment studies were conducted in Asia. It should be noted that several other IMERG assessment studies were conducted in Western countries, for example, [17,18], but they did not perform the daily scale assessment and were therefore excluded from this comparison. To date, the IMERG's daily precipitation was found to have a very good correlation with ground-based precipitation in China [16,38,46].…”
Section: Discussionmentioning
confidence: 99%
“…There have been fewer accuracy assessment studies of the IMERG than those for TMPA products as the IMERG product has been released recently. Some initial assessments of the IMERG have been conducted in China [16], the Netherlands [17], Western United States [18] and the upper Blue Nile basin [19]. Most of the studies found that the product is suitable to be used in hydro-climatic applications in their regions.…”
Section: Introductionmentioning
confidence: 99%
“…In mountainous regions, precipitation is extremely variable and there are changes in rainfall distribution over short distances. Additionally, higher altitudes mean that a large proportion of precipitation is in the solid phase, which is a challenge not only for satellites but also for rain gauges and weather radars [52]. A way to evaluate the performance of IMERG-F is by comparing it with the uncalibrated version of the product.…”
Section: Alps and Adriatic Seamentioning
confidence: 99%
“…While there have been several studies focused on evaluation of precipitation products in the mountains, the general consensus from the literature is that larger underestimations are incurred with increasing altitude for complex terrain in both warm and cold climates (Henn et al, 2018;Hong et al, 2007Hong et al, , 2004Wen et al, 2016). Global precipitation products have also been shown to disagree the most during winter in both event magnitude and the number of precipitation events (Behrangi, Andreadis, et al, 2014;Tian & Peters-Lidard, 2010;Maggioni et al, 2017), and at high elevation (Henn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%